Adoption and continued use of mobile contact tracing technology: multilevel explanations from a three-wave panel survey and linked data. Issue 1 (17th January 2022) - Horvath, Laszlo; Banducci, Susan; Blamire, Joshua; Degnen, Cathrine; James, Oliver; Jones, Andrew; Stevens, Daniel; Tyler, Katharine
Abstract : Objective: To identify the key individual-level (demographics, attitudes, mobility) and contextual (COVID-19 case numbers, tiers of mobility restrictions, urban districts) determinants of adopting the NHS COVID-19 contact tracing app and continued use overtime. Design and setting: A three-wave panel survey conducted in England in July 2020 (background survey), November 2020 (first measure of app adoption) and March 2021 (continued use of app and new adopters) linked with official data. Participants: N=2500 adults living in England, representative of England's population in terms of regional distribution, age and gender (2011 census). Primary outcome: Repeated measures of self-reported app usage. Analytical approach: Multilevel logistic regression linking a range of individual level (from survey) and contextual (from linked data) determinants to app usage. Results: We observe initial app uptake at 41%, 95% CI (0.39% to 0.43%), and a 12% drop-out rate by March 2021, 95% CI (0.10% to 0.14%). We also found that 7% of nonusers as of wave 2 became new adopters by wave 3, 95% CI (0.05% to 0.08%). Initial uptake (or failure to use) of the app associated with social norms, privacy concerns and misinformation about third-party data access, with those living in postal districts with restrictions on mobility less likely to use the app. Perceived lack of transparent evidence of effectiveness was associated with drop-out of use. In addition, those who trusted the government were more likely to adopt in wave 3 as new adopters. Conclusions: Successful uptake of the contact tracing app should be evaluated within the wider context of the UK Government's response to the crisis. Trust in government is key to adoption of the app in wave 3 while continued use is linked to perceptions of transparent evidence. Providing clear information to address privacy concerns could increase uptake, however, the disparities in continued use among ethnic minority participants needs further investigation.